Accountability Of Perpetrators Of Murder Accompanied By Rape Of A Minor (Judgment Study Number 580/Pid.B/2022/PN.Stb) - Susanti, Rulita; Sahlepi, Muhammad Arif; Ismaidar, Ismaidar (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Murder and rape are criminal acts regulated under the Criminal Code (KUHP). Murder that results in the unlawful death of a person is regulated under Article 338 of the KUHP, with a penalty of up to 15 years in prison. Meanwhile, rape involving violence or the threat of violence is regulated under Article 285 of the KUHP, with a penalty of up to 12 years in prison, as well as under Law No. 12 of 2022 on Sexual Violence Crimes. Murder accompanied by the rape of a minor is a concurrent criminal offense regulated under Article 340 of the KUHP and Article 285 of the KUHP. In addition, the Child Protection Law is regulated under Law No. 35 of 2014, as the victim in this case is a minor. In this case, the judge will consider various factors, including the prosecutor’s demands, the fulfilled elements, and aggravating and mitigating circumstances. This research uses a normative-empirical method by examining existing case studies. The purpose of this research is to understand the criminal law enforcement for holding perpetrators accountable for murder accompanied by the rape of a minor. The results of the study indicate that the perpetrators can be charged under applicable articles, including Article 80 (3) in conjunction with Article 76 C of Law No. 35 of 2014 on Child Protection. The perpetrators are also proven legally and convincingly guilty of committing acts of violence against a child that resulted in death. The defendant was sentenced to 13 (thirteen) years in prison and a fine of IDR 1,000,000,000 (one billion rupiah), or in default, six (6) months of imprisonment.